1998
DOI: 10.2190/b6vr-nnd7-46bl-py5g
|View full text |Cite
|
Sign up to set email alerts
|

Globalization in the Pharmaceutical Industry, Part II

Abstract: This is the second of a two-part report on the pharmaceutical industry. Part II begins with a discussion of foreign direct investment and inter-firm networks, which covers international mergers, acquisitions, and minority participation; market shares of foreign-controlled firms; international collaboration agreements (with a special note on agreements in biotechnology); and licensing agreements. The final section of the report covers governmental policies on health and safety regulation, price regulation, indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Pharmaceuticals can be divided into three categories: in-patent drugs, out-of-patent drugs, and generic and over-the-counter (OTC) drugs (Tarabusi and Vickery, 1995). This categorisation is in accordance with the typical business models of pharmaceutical companies associated with the regulatory regime.…”
Section: Scope Of the Pharmaceuticals Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceuticals can be divided into three categories: in-patent drugs, out-of-patent drugs, and generic and over-the-counter (OTC) drugs (Tarabusi and Vickery, 1995). This categorisation is in accordance with the typical business models of pharmaceutical companies associated with the regulatory regime.…”
Section: Scope Of the Pharmaceuticals Sectormentioning
confidence: 99%
“…Much attention has been paid to optimising the balance between providing adequate protection for new products and encouraging their widespread use (Tarabusi and Vickery, 1995). There have been a number of empirical studies on the economic impact of intellectual property, 126 and a subset of studies has focused specifically on pharmaceuticals.…”
mentioning
confidence: 99%
“…Companies such as Roche, Bristol-Myers Squibb, Abbott, Lilly, or Wyeth entirely closed down their infectious diseases divisions (Moran, 2005b: 9;Buse and Walt, 2000a: 552;Tarabusi andVickery, 1998a, 1998b). 2.…”
Section: Ghps As Response To Dual Market Failuresmentioning
confidence: 99%
“…Importantly, emerging markets such as Brazil, China, and India are rapidly becoming global players in the pharmaceutical industry, as both producers and consumers (Deutsch Bank Research, 2008). Table 18 Analysis by Taribusi and Vickery (1998) found that the pharmaceutical industry has been indeed undergoing major restructuring. This transition has been the result of a flurry of mergers and acquisitions as companies have sought to increase economies of scale (and with it cost savings, market access, and portfolios of products).…”
Section: Globalization and The Pharmaceutical Industrymentioning
confidence: 99%